The effects of chronic sodium bicarbonate ingestion and interval training in highly trained rowers - Driller, M. W.; Gregory, J. R.; Williams, A. D.; Fell, J. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Recent research has reported performance improvements after chronic NaHCO3 ingestion in conjunction with high-intensity interval training (HIT) in moderately trained athletes. The purpose of the current study was to determine the effects of altering plasma H+ concentration during HIT through NaHCO3 ingestion over 4 wk (2 HIT sessions/wk) in 12 Australian representative rowers (M ± SD; age 22 ± 3 yr, mass 76.4 ± 4.2 kg, VO2peak 65.50 ± 2.74 ml · kg-1 · min-1). Baseline testing included a 2,000-m time trial and an incremental exercise test. After baseline testing, rowers were allocated to either a chronic NaHCO3 (ALK) or placebo (PLA) group. Starting 90 min before each HIT session, subjects ingested a 0.3-g/kg body mass dose of NaHCO3 or a placebo substance. Fingertip blood samples were taken throughout the study to analyze bicarbonate and pH levels. The ALK group did not produce any additional improvements in 2,000-m rowing performance time compared with PLA (p > .05). Magnitude-based inferential analysis indicated an unclear or trivial effect on 2,000-m power, 2,000-m time, peak power output, and power at 4 mmol/L lactate threshold in the ALK group compared with the PLA group. Although there was no difference between groups, during the study there was a significant mean (± SD) 2,000-m power improvement in both the ALK and PLA groups of 17.8 ± 14.5 and 15.2 ± 18.3 W, respectively. In conclusion, despite overall improvements in rowing performance after 4 wk of HIT, the addition of chronic NaHCO3 supplementation during the training period did not significantly enhance performance further.